PSXI-21 Supplementation of ruminal aflatoxins-detoxifying bacteria on in vitro nutrients digestibility and aflatoxin B1 detoxification. (7th December 2018) - Intanoo, M; Pattarajinda, V; Bernard, J; Callaway, T
Abstract: Aflatoxin B1 (AFB1 ) is the most prevalent mycotoxin produced by Aspergillus flavus . It is classified as a group 1 carcinogen and when consumed by young animals can be extremely toxic. Long-term intake of AFB1 by lactating dairy cows reduces feed efficiency and milk production. Previous research has reported that AFB1 can be degraded by certain rumen microbes. The objective of this in vitro study was to examine the effect of isolated ruminal bacterial with AFB1 detoxifying potential on in vitro nutrient digestibility and AFB1 detoxification. The completely randomized design included ten treatments; including a control and three bacterial isolates with AFB1 detoxification properties supplemented at three concentrations. Each incubation contained 200 ppm AFB1 in nutrient broth media (10 mL). Bacterial isolates were identified as Enterococcusfaecium (CPB6), Corynebacterium phoceense (RSB1), and C. vitaeruminis (YSB3), and these were included at: 10 7, 10 8 or 10 9 CFU/mL. An interaction ( P < 0.01) between isolates and concentration was observed for DM digestibility because of lower digestibility for RSB1 and YSB3 supplemented at 10 7 CFU/mL compared with CPB6 at all concentrations, and RSB1 and YSB3 at 10 9 CFU/mL. No differences ( P > 0.05) were observed in NDF or ADF digestibility among treatments. Degradation of AFB1 after 48 h of incubation was maximal for: all concentrations of CPB6, YSB3 incubations containing 10 8 and 10 9 CFU/mL; and RSB1 incubations containing 10 9 CFU/mL compared with remaining treatments ( P < 0.01). Results of this trial indicated that supplementing AFB1 detoxifying bacteria at 10 9 CFU/mL degraded over 68% of AFB1 without any adverse effect on in vitro DM, NDF or ADF digestibility. These bacterial isolates offer an alternative approach to reduce aflatoxins contamination in milk and dairy products.